Optimization of Energy Consumption in The Residential Sector, Using Automated Control Systems; The European Proceedings of Social & Behavioural Sciences (EpSBS); Vol. 26 : Responsible Research and Innovation (RRI 2016) - Zhdanova A. B. Anna Borisovna; Rakhimov T. R. Timur Rustamovich; Bannova K. A. Kristina Alekseevna; Khudyakova G. S.; Krivoshein Y. O. (2017, 2017)
Title screen